Post-COVID-19 syndrome and its sequelae: a cross-sectional study - Hemat Allam; Mai S. Elsheikh; Ahmad Elwahidy; Rasha Monir; Amira Medhat; Yasmin M. Ziada; Ahmed Gharib; Gehan Hamdy (The Egyptian Journal of Bronchology, 2024)
Abstract Background The long-term post-COVID is a very complex pandemic phenotype disease. The persistence of manifestations had resulted in classifying COVID-19 infection into bipolar phase which is a post-COVID-19 subacute phase by which the ongoing symptoms extended for 4–12 weeks and chronic or long COVID-19 phase by which the associated symptoms and abnormalities were extending for more than 12 weeks even after the pandemic. Aim Determining the percentage of patients who continued to suffer from different symptoms beyond 12 weeks of COVID-19 exposure and the use of different complementary modalities among patients with post-COVID. Patients and methods The present study is a cross-sectional analytical observational study which was conducted through an online questionnaire using Google Forms with a total sample of 123 Egyptian patients older than 30 years old diagnosed with symptomatic and/or laboratory-confirmed COVID-19 infection with persistent health problems over 12 weeks prior to December 2021. Result The findings revealed elevated percentages of persistent symptoms and unfavorable long-term consequences extending beyond 12 weeks post-infection, irrespective of vaccination status or hospitalization. These outcomes significantly affected individuals’ health, finances, family dynamics, and lifestyle. Additionally, a notable proportion of cases sought relief through complementary medicine, particularly probiotics and herbal remedies. Conclusion The questionnaire is an addition for a comprehensive long-term evaluation that might aid the clinician for follow-up of patient infected with COVID-19 and broaden the use of various complementary medical disciplines.